2019
DOI: 10.1111/tme.12627
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of Borrelia circulation among blood donors in the São Paulo state, Brazil

Abstract: SUMMARY Objective The objective of this study was to examine the Borrelia seroprevalence among blood donors in Southeast Brazil. Background There is evidence that Borrelia spirochetes are circulating in Brazil; however, there are no studies that characterise these bacteria and investigate their seroprevalence in the Brazilian population. Such a situation, combined with a recent outbreak of tick‐borne Rocky Mountain spotted fever in the São Paulo state demonstrates the increasing role of ticks as arthropod vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Even though Brazilian Borrelia disease (BBD) is not notified, many cases have increased. The prevalence of IgG antibodies to Borrelia was 3.5% (16 samples) [28]. Bonoldi et al showed that BBD patients with clinical symptoms presented 50% (14/28) positive serology in the acute phase (<3 months) and 45% (10/22) positive serology in the later phase (>3 months) [29].…”
Section: Introductionmentioning
confidence: 99%
“…Even though Brazilian Borrelia disease (BBD) is not notified, many cases have increased. The prevalence of IgG antibodies to Borrelia was 3.5% (16 samples) [28]. Bonoldi et al showed that BBD patients with clinical symptoms presented 50% (14/28) positive serology in the acute phase (<3 months) and 45% (10/22) positive serology in the later phase (>3 months) [29].…”
Section: Introductionmentioning
confidence: 99%